2006
DOI: 10.3354/meps320169
|View full text |Cite
|
Sign up to set email alerts
|

Re-colonisation rate differs between co-existing indigenous and invasive intertidal mussels following major disturbance

Abstract: The potential of introduced species to become invasive is often linked to their ability to colonise disturbed habitats rapidly. We studied the effects of major disturbance by severe storms on the indigenous mussel Perna perna and the invasive mussel Mytilus galloprovincialis in sympatric intertidal populations on the south coast of South Africa. At the study sites, these species dominate different shore levels and co-exist in the mid mussel zone. We tested the hypotheses that in the midzone P. perna would suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 45 publications
1
39
0
1
Order By: Relevance
“…The major gamete production was more protracted for Perna perna (4 mo) than for Mytilus galloprovincialis (2 mo) and maximum GSI was much greater for the invasive species. It has been shown that M. galloprovincialis has a very high reproductive output (van Erkom Schurink & Griffiths 1991, Harris et al 1998, which, together with fast growth, and the ability to colonise free space very rapidly (Erlandsson et al 2006) could be responsible for allowing it to become the most abundant alien marine species in South Africa (Robinson et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The major gamete production was more protracted for Perna perna (4 mo) than for Mytilus galloprovincialis (2 mo) and maximum GSI was much greater for the invasive species. It has been shown that M. galloprovincialis has a very high reproductive output (van Erkom Schurink & Griffiths 1991, Harris et al 1998, which, together with fast growth, and the ability to colonise free space very rapidly (Erlandsson et al 2006) could be responsible for allowing it to become the most abundant alien marine species in South Africa (Robinson et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Also on the east coast of South Africa local people have mainly been harvesting bivalves and gastropods, reducing the intertidal mussel beds there to almost non-existence, with a change in community structure and dramatic declines in biodiversity and ecosystem function (Lasiak 1991;Dye 1992;Lasiak and Field 1995). These mussel beds also have extreme difficulties to recover through natural recruitment, since there are strong adult-recruit relationships and high post-settlement mortality (Erlandsson et al 2006;Erlandsson et al 2008). This is also an example of the classic theory "the tragedy of the commons", which will deplete biological resources and impoverish local people (Hardin 1998).…”
Section: Comparison Between Exploited and Inaccessible Sitesmentioning
confidence: 99%
“…The arrival of this invasive species has caused major changes in the structure and functioning of intertidal communities on these rocky shores (Robinson et al 2007). Because of its higher physiological performances, dispersal rates and ability to colonize free space (Branch & Steffani 2004, Erlandsson et al 2006, this invasive species has replaced the indigenous mussels Aulocomya ater and Choromytilus meridionalis as the dominant mussel on the mid and low shores on the west coast (Robinson et al 2007). Moreover M. galloprovincialis outcompetes adult limpets (Scutellastra argenvillei and S. granu laris) for primary space on exposed rocky shores on the west coast (Hockey & van Erkom Schurink 1992, Steffani & Branch 2003.…”
Section: Introductionmentioning
confidence: 99%